Efici??ncia energ??tica em escolas ??? estudo de caso escola estadual Padre Ant??o de S??o Paulo - Vieira, Amanda Cleomacles de Mesquita (2019)
Buildings are one of the main sources of energy consumption in cities, as well as the emission of greenhouse gases due to their generation. The phase of operation of buildings is the one involving the highest energy consumption throughout its life cycle. For old buildings, several authors indicate that there is a huge energy saving potential to be studied. The general objective of the work is to propose actions for the improvement of energy efficiency at the State School Padre Ant??o / SP, based on PROCEL-Edifica criteria. The work was developed through a case study. Data collection involved site visits and unstructured interviews, as well as obtaining documents, records, and building engineering data. The data analysis was done using the PROCEL-Edifica simulation method through the use of the EnergyPlus software, which obtained the classification of the energy demand as label A, and in relation to the percentage of hours occupied in label comfort C; therefore, the general classification of the building obtained was labeled C. For practical purposes, the implications of this work are in the indications of the improvements proposed to increase the energy efficiency in the buildings. Some of the potential improvements identified were: changing from fluorescent lamps to LEDs, altering lighting circuits and improving vertical shading of facades by means of brises. A basic analysis of the time of return of investment for some improvements was made, demonstrating possible prioritization of actions. In general, the simulated real model is calibrated. However, the classification of the building is questionable due to some evaluation criteria of PROCEL-Builds for simulated reference models such as the power density of illumination in the lighting systems item. As well as the envelope criteria, which interfere very little with models with natural ventilation, these determinations are better evaluated by models with air conditioning.